2020
DOI: 10.1007/s00227-020-03712-y
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of diverse movement strategies and habitat use by white sharks, Carcharodon carcharias, off southern Australia

Abstract: Large endothermic pelagic sharks are highly migratory and use habitats spanning a broad range of coastal, neritic and oceanic areas. This study aimed to resolve the current lack of information on the movements and habitat use of white sharks, Carcharodon carcharias, between shelf, slope and oceanic areas located off southwestern Australia. Movement behaviours, spatial distribution patterns and vertical habitat use of juvenile, sub-adult and adult white sharks ranging in size from 1.9 to 5.7 m total length were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 44 publications
(50 reference statements)
11
18
0
Order By: Relevance
“…There are two plausible explanations for this result. First, white shark residency is not primarily driven by the attractants used but is linked to their natural migratory patterns ( Bradford et al, 2020 ) and their use of the Neptune Islands to feed on pinnipeds and teleosts ( Meyer et al, 2019 ). Alternatively, considering the intensity of cage-diving tourism with boats present at the Neptune Islands nearly every day over the last 12 years ( Tanner et al, 2019 ), it may be that the presence of the cage-diving industry induced a more pervasive change that was not alleviated by a 1.5-month break in tourism.…”
Section: Case Study: Residency and Activity Space Of White Sharks And Yellowtail Kingfish At A Popular Wildlife Tourism Sitementioning
confidence: 99%
“…There are two plausible explanations for this result. First, white shark residency is not primarily driven by the attractants used but is linked to their natural migratory patterns ( Bradford et al, 2020 ) and their use of the Neptune Islands to feed on pinnipeds and teleosts ( Meyer et al, 2019 ). Alternatively, considering the intensity of cage-diving tourism with boats present at the Neptune Islands nearly every day over the last 12 years ( Tanner et al, 2019 ), it may be that the presence of the cage-diving industry induced a more pervasive change that was not alleviated by a 1.5-month break in tourism.…”
Section: Case Study: Residency and Activity Space Of White Sharks And Yellowtail Kingfish At A Popular Wildlife Tourism Sitementioning
confidence: 99%
“…Neonates and YOYs of oceanic species are considered to be more wide ranging, and their distributions may be more vertically limited compared to adults (Afonso and Hazin, 2015;Carlisle et al, 2015;Hoyos-Padilla et al, 2016;Vandeperre et al, 2016;Coffey et al, 2017). However, while white sharks exhibit an offshore, oceanic phase as adults, YOY individuals [<175 cm total length (TL)] are predominantly found in coastal habitats, which suggests that although birthing in white sharks has not been observed and parturition habitats are unknown, parturition may occur proximally to the nearshore environment (Dewar et al, 2004;Weng et al, 2007a,b;Jorgensen et al, 2012;Domeier and Nasby-Lucas, 2013;Lyons et al, 2013;Harasti et al, 2017;Curtis et al, 2018;Bruce et al, 2019;White et al, 2019;Bradford et al, 2020;Spaet et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Sharks mostly remained within shelf waters in depths < 100 m with occasional dives to depths > 1000 m. During Miocene period, megalodon was estimated has traveled to deepest parts of Indian ocean located in South of West Java coast. As a comparison, extant great white shark has travelled over a long distance exceeding an estimated 1000 km in length (Bradford et al 2020). Megalodon juvenile was modeled having higher habitat preferences at shallow water near the coast and at depth of > 200 m. Based on observation of extant shark, Weng et al (2007) have reported juvenile sharks have occasionally displayed deeper movements and vertical excursions reaching depth of 226 m. Shallow water excursions at depth of 26 m were observed mainly during dawn, day and dusk.…”
Section: Discussionmentioning
confidence: 99%